1999
DOI: 10.1002/(sici)1096-8628(19991105)87:1<23::aid-ajmg5>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium of MTHFR genotypes 677C/T‐1298A/C in the German population and association studies in probands with neural tube defects(NTD)

Abstract: A number of studies have demonstrated that the common polymorphism 677C-->T in the gene encoding 5, 10-methylenetetrahydrofolate reductase (MTHFR) leads to a thermolabile variant with decreased enzyme activity and to mildly elevated plasma homocysteine. 677TT homozygosity was shown to be more frequent in NTD probands compared with controls in some studies. Recently, another polymorphism, 1298A-->C, in the MTHFR gene was described and combined heterozygosity 677CT/1298AC was suggested to be an additional risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
2
4

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 0 publications
10
33
2
4
Order By: Relevance
“…35 It is interesting that individuals with homozygous mutations at one site always were homozygous wild-type at the other site, suggesting embryonic selection because of a lethal effect of double homozygotes of these 2 variants or a possible founder effect. This finding is also consistent with those in Caucasians by Stegmann et al 31 In this study, the risk associated with MTHFR 677TT and 677CT genotypes was more pronounced in gastric cardia cancer, which is anatomically adjacent to the esophagus and may share an etiology similar to that of esophageal cancer. 27 This finding suggests different genetic susceptibility to gastric cancer at different sites, which is consistent with the findings of different epidemiologic characteristics, etiology, pathogenesis and clinical behavior reported for gastric cancer at different sites.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…35 It is interesting that individuals with homozygous mutations at one site always were homozygous wild-type at the other site, suggesting embryonic selection because of a lethal effect of double homozygotes of these 2 variants or a possible founder effect. This finding is also consistent with those in Caucasians by Stegmann et al 31 In this study, the risk associated with MTHFR 677TT and 677CT genotypes was more pronounced in gastric cardia cancer, which is anatomically adjacent to the esophagus and may share an etiology similar to that of esophageal cancer. 27 This finding suggests different genetic susceptibility to gastric cancer at different sites, which is consistent with the findings of different epidemiologic characteristics, etiology, pathogenesis and clinical behavior reported for gastric cancer at different sites.…”
Section: Resultssupporting
confidence: 92%
“…Because the C677T and A1298C variant genotypes affect in vitro MTHFR activity and are correlated with blood homocysteine levels, 23,31 their association with cancer risk is of great interest. The MTHFR enzyme is part of a complex metabolic entity involving both generation of the universal methyl-group donor S-adenosylmethionine and DNA synthesis via the creation of nucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for the MLLϩ leukemias, there was no evidence of a protective effect for the A1298C variant (AC ϩ CC, OR ϭ 1.62 with a 95% CI of 0.78-3.36; Table 2). An OR of greater than one indicates that the variant is an ''at risk'' allele; however, it must be noted that the two alleles are in tight negative linkage disequilibrium (28). After adjusting for the nucleotide 677, the A1298C OR falls close to unity (OR ϭ 1.14 with a 95% CI of 0.49-2.73).…”
Section: Resultsmentioning
confidence: 96%
“…These data corroborate several earlier investigations in the field. 3,19,20,33 As the physical distance of 2.1 kb between the two polymorphisms is short, it is not surprising that recombination events very rarely have been observed. 19,34,35 However, these and our results are in apparent contradiction with those reported in two studies by Isotalo et al 21,36 who found a substantial number of combined MTHFR 677TT/1298AC genotypes in adults (approximately 10% of the study participants), 36 neonates (1.7%) 21 and aborted embryos (1.2%), 21 and 677CT/1298CC and 677TT/1298CC genotypes selectively in aborted embryos (3.7%).…”
Section: Discussionmentioning
confidence: 99%